The Authenticity Cascade: How CSR Shapes Brand Love and Loyalty Among Young Indonesian Coca-Cola Consumers - Purnama, Anggelina (Manunggal Halim Jaya, 2026)
Despite the widespread adoption of Corporate Social Responsibility (CSR), consumers remain suspicious and skeptical about companies’ true motives, making it essential to understand how authentic CSR affects brand loyalty (brand trust, positive word-of-mouth (PWoM), and repurchase intention) through the underlying mechanisms of brand authenticity and brand love, particularly among younger generations. This study examines the impact of CSR authenticity on brand loyalty among Indonesian Millennials and Generation Z Coca-Cola consumers, considering brand authenticity and brand love as mediators, and brand image as a moderator. Data was collected through an online survey of 292 Millennial and Gen Z Coca-Cola consumers in Indonesia and was analyzed using PLS-SEM. CSR authenticity positively influences brand loyalty through brand authenticity and brand love. The results showed that 14 out of 15 proposed hypotheses were supported. According to the attribution theory, when consumers perceive CSR as genuine, they perceive the brand as authentic and develop a positive attitude towards it; therefore, they are more likely to trust the brand, recommend it to others, and make repeat purchases. The results will help marketers develop authentic CSR strategies that effectively build brand loyalty among young consumers.